Musculoskeletal symptoms in professional musicians - Silva, Lídia Maria Lopes da (2022)
The objective of this study was to evaluate the presence and severity of musculoskeletal (MS) symptoms in the trunk and upper limbs of keyboardists. Cross-sectional study, including volunteers of both genders, aged 18-40 years, who practiced for at least 2 years, excluding those with systemic diseases, were assessed for MS pain using the Nordic Musculoskeletal Questionnaire. The χ-squared test was used for statistical analysis and a significance level of 5% was adopted. This study was approved by the Ethics Committee of the Ceuma University (opinion nº 2,627,609). Thirty-nine volunteers were evaluated, and all reported experiencing pain or discomfort. The regions of greatest complaint of chronic pain/discomfort were the thoracic and lumbar spine (n = 27 ,69.24%; p <0.05) and wrist/hand (n = 23.58.9%). The highest acute complaint was in the lumbar spine (n = 12, 30.76%; p <0.05), and in the wrist/hand (n = 9, 23.07%). A severity index of 1 was the most frequent (n = 14, 36%). It can be concluded that keyboardists have MS mainly in the spine, wrist, and hands, although the severity of the symptoms is mild; the high frequency of complaints suggests the importance of prevention and treatment of musculoskeletal symptoms before aggravation.